The Photo Narrative Process: Students’ Intercultural Learning in Agriculture - Emily Bost; Gary Wingenbach (Journal of International Agricultural and Extension Education, 2018)
Cultural heritage describes our way of life. It comes from previous generational traditions and incorporates our current constructed and natural environments, and tangible artifacts. The photo narrative process, derived from photovoice, combines photography and narrative expression about artifacts important to one’s way of life. The purpose of this study was to explore effects of the photo narrative process on students’ intercultural learning in agriculture. Photo narrative assignments were developed for students to capture facets of their cultural heritage, and their host countries’ cultural heritage fromthree separate study abroad programs. Archival data werecollected (i.e., course assignments to illustrate one’s cultural heritage via photo and text)andvisual social semiotics wereused to analyze data.TheDevelopmental Model of Intercultural Sensitivity provided context forstudents’ levels of intercultural competence. The results showed participants experienced frame shifts (i.e., perspective change in worldviews) from ethnocentrism to ethnorelativism, as evidenced in the rhetoric of their artifacts after participating in thephoto narrative process. The photo narrative processis a valuable educational technique;its purposeful usehelpslearners experience and progress through the stages of intercultural competence. Photo narrative takes advantage ofyoung people’s preferred communication methods (i.e., social media), combiningimage and text, which empowers themthrough expressive communication and reflection.Purposeful photo narrative processes may be adapted to help learnersexploreperspective shifts in racism, classism,orreligionto increase understanding andempathetic response between dissimilar groups
Keywords: Intercultural competence; photo narrative; cultural heritage